Dynamic risk management approach using immune system - Sarkheyli, Azadeh (2011)
Risks include the factors that might adversely affect on project outcomes. Risk analysis includes the processes concerned with identifying, analyzing and developing security strategy and plans for the factors. Although currently there are methodologies known such as (CCTA Risk Analysis and Management Method (CRAMM) or Consultative, Objective and Bi-functional Risk Analysis (COBRA) etc. for Risk Management, they have common failure for instance no specific function which recover/avoid risks/attacks toward IS/IT component and poor executive support, high cost of implementation, untimely response, insufficient accountability, inability to qualitatively measure control environment, infrequent in assessment, inaccurate data. Hence, these problems and the importance of IS/IT Risk Management cause the research to organize a dynamic risk management approach by making them intelligent as like as the immune system which is a complete system and could be the best model for simulating Risk Management in the organizations. However, the results of this study could help organizations toward improving IS/IT Risk Analysis process which are designed and proposed by investigation about their current procedure and problems of Risk Management.